A hepatitis C outbreak preceded the HIV outbreak among persons who inject drugs in Athens, Greece: Insights from a mathematical modelling study. Issue 11 (18th August 2019) - Gountas, Ilias; Sypsa, Vana; Papatheodoridis, George; Paraskevis, Dimitrios; Kalamitsis, George; Anagnostou, Olga; Antaraki, Argiro; Fotiou, Anastasios; Hatzakis, Angelos
Abstract: People who inject drugs (PWID) comprise one of the major transmission risk groups for human immunodeficiency virus (HIV) and hepatitis C virus (HCV). In 2011, Athens experienced a large HIV outbreak among PWID. Significant public health interventions were implemented in response to the HIV outbreak. The aims of this study were to estimate the indirect effects of the HIV interventions on HCV infection and to evaluate the concept of the association between HCV and HIV infections in the case of Athens. A dynamic, stochastic, individual‐based model was developed to simulate HCV transmission among PWID. We calibrated the model to reproduce the observed HCV prevalence among PWID in Greece. Two years prior to the HIV outbreak, an undetected HCV outbreak has occurred. In 2009, the incidence of HCV infection increased from 640 (495, 842) cases in 2008 to 1260 (1060, 1500). The mean time from initiation of injecting drug use to HCV acquisition decreased from 29 months in 2008 to 13 months in 2009. After HIV interventions, HCV incidence declined by 64.8% in 2012, compared to 2009. The averted HCV incidence cases attributed to the HIV‐implemented interventions were 2200 (1950, 2480), during 2012‐2015. The cumulative number incident HCV cases in Athens during 2002‐2015 was about 9900 (7800, 12 100). Our results highlight that before the 2011 HIV outbreak in Athens, an HCV outbreak occurred in 2009. Prevention measures for HIV that took place in the Athens metropolitan area in 2012 reduced significantly the incidence of HCV.